The Digital Divide in Technologies for Autism: Feasibility Considerations for Low- and Middle-Income Countries. - Kumm, Aubrey J.; Viljoen, Marisa; de Vries, Petrus J. (Journal of Autism & Developmental Disorders, 2022)
Digital technologies have the potential to empower individuals with autism and their families. The COVID-19 pandemic emphasized and accelerated the drive towards technology for information, communication, training, clinical care and research, also in the autism community. However, 95% of individuals with autism live in low- and middle-income countries (LMIC) where access to electricity, internet and the ever-increasing range of digital devices may be highly limited. The World Bank coined the term 'the digital divide' to describe the disparities in access to digital technologies between high-income and LMIC contexts. Here we evaluated the feasibility of six emerging technologies for autism spectrum disorders, and reflected on key considerations for implementation in LMIC contexts to ensure that we do not inadvertently widen the pre-existing digital divide.